Carcass wrote:
If the average of m and \((x + y)^2 = x^2 + y^2\) , what is the value of m ?
A. x-y
B. x+y
C. (x-y)(x+y)
D. \((x-y)^2\)
E. \((x+y)^2\)
The average of m and (x + y)² = x² + y²So: [m + (x + y)²]/2 = x² + y²
Multiply both sides by 2 to get: m + (x + y)² = 2x² + 2y²
Expand left side to get: m + x² + 2xy + y² = 2x² + 2y²
Subtract x² from both sides to get: m + 2xy + y² = x² + 2y²
Subtract y² from both sides to get: m + 2xy = x² + y²
Subtract 2xy from both sides to get: m = x² - 2xy + y²
Factor right side to get: m = (x - y)²
Answer: D
Cheers,
Brent